Throughput optimization of dynamic OFDM-FDMA systems with inband signaling - Gross, James; Karl, Holger; Wolisz, Adam (2nd International Symposium on Modeling and Optimization in Mobile, Ad Hoc, and Wireless Networks 2004 (WiOpt 2004))

A Runtime Environment for Reconfigurable Hardware Operating Systems - Walder, Herbert; Platzner, Marco (Proceedings of the 14th International Conference on Field Programmable Logic and Applications (FPL))

XF-BOARD: A Prototyping Platform for Reconfigurable Hardware Operating Systems - Walder, Hebert; Nobs, Samuel; Platzner, Marco (Proceedings of the 4th International Conference on Engineering of Reconfigurable Systems and Algorithms (ERSA))

Efficient Execution of Process Networks on a Reconfigurable Hardware Virtual Machine - Dyer, Matthias; Platzner, Marco; Thiele, Lothar (Proceedings 12th Annual IEEE Symposium on Field-Programmable Custom Computing Machines (FCCM))

Aus dem Italienischen ins Deutsche: F. D’Agostini, Che cosa significa essere una donna? Le basi ontologiche della differenza di genere tra analisi concettuale e teoria politica

,Aber vielleicht kommt noch eine Zeit, wo auch meine Arbeiten wieder entdeckt und gelesen werde‘: Die gescheiterte Karriere des Ernst Zermelo - Peckhaus, Volker (Mathematik im Fluß der Zeit. Tagung zur Geschichte der Mathematik in Attendorn/Neu-Listernohl (28.5. bis 1.6.2003))

Otto Friedrich Gruppe und die Logische Frage - Peckhaus, Volker (Otto Friedrich Gruppe 1804–1876. Philosoph, Dichter, Philologe)
Rezension: Journal of the History of Philosophy 43.3 (2005), 367–369 (H.J. Cloeren).

Paradoxes in Göttingen - Peckhaus, Volker (One Hundred Years of Russell's Paradox. Mathematics, Logic, Philosophy)

Garantiert Widerspruchsfreiheit Existenz? - Peckhaus, Volker (Was folgt? Themen zu Wessel)

Dignaga’s Logic of Invention - Peckhaus, Volker (History of the Mathematical Sciences)
Rezension: Zbl. Math. 1049.01008 (A. C. Lewis).

Schröder’s Logic - Peckhaus, Volker (Handbook of the History of Logic, Bd. 3: The Rise of Modern Logic: From Leibniz to Frege)

Scholz als Metaphysiker - Peckhaus, Volker (Heinrich Scholz: Logiker, Philosoph, Theologe)

Who was Wilhelm Schlötel? - Peckhaus, Volker (Filosofisia tutkielmia - Philosophical Studies in honorem Leila Haaparanta)

Novel Modulation Schemes for Conventional and Sparse Matrix Converters Facilitating Reactive Power Transfer Independent of Active Power Flow - Schafmeister, Frank; Kolar, Johann (Proc. 35th IEEE Power Electronics Specialists Conference (PESC))

Enhanced Control Scheme for Three-Phase / Three-Level Rectifiers at Partial Load - Ide, Peter; Schafmeister, Frank; Fröhleke, Norbert; Grotstollen, Horst (Proc. 35th IEEE Power Electronics Specialists Conference (PESC))

Novel Hybrid Modulation Schemes Extending the Reactive Power Control Range of Conventional and Sparse Matrix Converters Operating at Maximum Output Voltage - Schafmeister, Frank; Kolar, Johann (Proc. 11th International Power Electronics and Motion Control Conference (EPE-PEMC))

Active Suppression of Torsional Oscillations - Böcker, Joachim; Amann, Notker; Schulz, Bernd (IFAC Proceedings Volumes)
Keywords: General Medicine

Active Damping of Drive Train Oscillations for an Electrically Driven Vehicle - Amann, Notker; Böcker, Joachim; Prenner, Franz (IEEE/ASME Transactions on Mechatronics)
Keywords: Electrical and Electronic Engineering; Computer Science Applications; Control and Systems Engineering

Tolerance band controller for a three-level four-quadrant converter including DC link balancing - Böcker, Joachim (2004 IEEE 35th Annual Power Electronics Specialists Conference (IEEE Cat. No.04CH37551))

Derivation of integrated magnetic components using reluctance and mathematical modeling - Njiende, H.D.; Fröhleke, N.; Böcker, Joachim (2004 IEEE 35th Annual Power Electronics Specialists Conference (IEEE Cat. No.04CH37551))